(untitled) (Groundings Undergraduate, 2024)
The COVID-19 pandemic has profoundly impacted global public health systems and economic frameworks. Many researchers have delved into these effects and widely discussed the ramifications. Building upon existing literature, this paper comparatively analyses the strategies adopted by France and Sweden in responding to the COVID-19 outbreak, emphasising the effectiveness and implications of the approaches undertaken by countries with centralised versus decentralised political systems to overcome COVID-19. Through comprehensive review of literature, news reports, and other sources, this study reveals psychological resistance and disdain towards COVID-19 vaccination among the populace under France’s centralised government system, alongside significant issues of “Tyranny of Experts” within Sweden’s decentralised governance framework.